“Control de convencionalidad para garantizar el derecho de igualdad en la determinación sexo/género en la cédula de ciudadanía en Ecuador - Doménica Belén, Cadena Castro (2020)
The right to formal equality, material equality and non-discrimination is one of the pillars that underpin the fundamental rights in the Constitution of 2008. Thus, to protect such fundamental rights, institutional and procedural mechanisms were created. So that, they allow that any person who feel their rights violated can access to an expedited, impartial justice that guarantees due process. These mechanisms are especially important for the protection of the rights of minorities such as LGBTI person. This group are usually victims of discrimination as a result of the inclusion of the sex or gender fields in the ID card, when their biological sex does not match the gender that they attribute themselves. To reduce or eliminate this source of discrimination on the ground of sex or gender this research work proposes that section 6 of article 94 of the Organic Law of Identity and Civil Data can be eliminated. Trough the control of conventionality that the Constitutional Court of Ecuador must exercise, as it did in the same-sex marriage ruling, to adapt the internal legal system to international human rights instruments and the jurisprudence of the CIDH. Especially its Advisory Opinion OC24 / 17 of 2017. To carry out this research work, a study of the control of conventionality, the control of constitutionality, the fundamental right to equality and non-discrimination and the main ways through which the proposed proposal could be analyzed. The most appropriate is the control of conventionality, complemented with the control of constitutionality.